Pendidikan Seni Rupa Dan Implikasinya Terhadap Imajinasi Kreatif Dan Sosial Emosional Anak Usia Dini Di TK Mekarraharja - Lita, Lita (Indonesian Journal of Islamic Early Childhood Education, 2018)
This study aims to describe the design of art learning in development of the creative imagination and social emotional of early childhood. The visual art learning process is visible in: 1) Learning design which includes: a) The purpose, that is to find out the whole childrens education and fulfill their needs. b) There are several types of visual art activities that can be given in early childhood such as drawing, painting, plagiarism, labeling, collage, sticking, splitting, folding, shaping, cutting, sewing, matching, arranging beads, batik painting. c) Methods used are methods of play and demonstration methods. d) Facilities and infrastructure sufficient. e) Evaluation used is evaluation of process, work, and portfolio. f) Social and cultural conditions strongly support. g) The supporting factor is that the media for visual art learning is easy to get, while the inhibiting factor is the unavailability of special space for art learning. 2) The development of childrens creative imagination develop according to expectations, it can be seen from the ideas and initiative of children as stated in their work. 3) The childrens social emotion develops as expected, the children are free to express their  feelings through various art media. Keywords: visual art education, creative imagination, social emotional